Global education digest... comparing edu cation statistics across the world. - UNESCO Institute for Statistics (Montreal : UNESCO Institute for Statistics, 2003)
It is a fundamental reference work for a general readership interest ed in comparing education systems and trends across the nations. The PD F publication provides an additional analysis of measures of educationa l participation, progression and completion.
Latest issue consulted: 2003.
Tutorial movies provided on this CD-ROM are created using TechSmith' s Camtasia video production toolkit. In order to play media files creat ed with TSCC by Camtasia you need the TechSmith Screen Capture Codec (T SCC) installed on your system. The UIS2003.exe program in the root dire ctory of this CD-ROM checks for the presence of TSCC and installs it if needed.
English and French.
Issued by: UNESCO Institute for Statistics
Keywords: Educational indicators -- Cross-cultural studies; Education